Etiologic Agents and Diseases Found Associated with Clinical Aspergillosis in Falcons - Walter Tarello (International Journal of Microbiology)
The aim of this study was to describe parasitological, microbiological, and pathological findings associated with the isolation of Aspergillus species in 94 clinically diseased captive falcons from Dubai. Concomitant agents and/or diseases were identified in 64 cases, causing either single (𝑛=36) or multiple coinfections (𝑛=28). Diagnoses found more often in association with aspergillosis were chronic fatigue and immune dysfunction syndrome (CFIDS) (𝑛=29), Caryospora sp. (𝑛=16), Serratospiculum seurati infestation (𝑛=14), cestodiasis (𝑛=6), bumblefoot (𝑛=5), trematodosis due to Strigea falconispalumbi (𝑛=5), trichomoniasis (𝑛=4), Babesia shortti (𝑛=4), Mannheimia (Pastorella) haemolytica (𝑛=4), interstitial hepatitis (𝑛=4), Escherichia coli (𝑛=3), and Clostridium perfringens enterotoxemia (𝑛=2). Compared with a control group of 2000 diseased falcons without evidence of aspergillosis, the prevalence of Babesia shortti, CFIDS, Mannheimia (Pastorella) haemolytica, Escherichia coli, and falcon herpes virus infection was conspicuously higher in association with aspergillosis. These entities may be considered suitable candidates as predisposing factors for the mycosis.